Efeitos de mindfulness no padrão de uso crônico de hipnóticos e na insônia entre mulheres insones que buscam por tratamento - Barros, Viviam Vargas de [UNIFESP] (2017)
Objectives: 1) To evaluate the profile of women who chronically use hypnotics and seek for treatment, and the association between hypnotics dependence and dispositional mindfulness in this population. 2) To evaluate the impact of the Mindfulness-Based Relapse Prevention program on the insomnia and hypnotics reduction in this population, over six months postintervention, in a clinical setting. Methods: The research was composed by two studies. The Study 1 was a cross-sectional study and comprised a sample of 76 women in chronic use of hypnotics who lived in São Paulo and voluntarily sought the MBRP program for the reduction or cessation of hypnotics use after disclosure of the project in the media. They answered questionnaires about demographics, dispositional mindfulness (FFMQ-BR), hypnotics dependence (BENDEP-SRQ-PV), insomnia severity (ISI) and anxiety trait (STAI-T). Study 2 was a randomized controlled trial and its sampla was composed by the participants of Study 1. After 6 dropouts, 70 participants were randomized to intervention group – IG (36), which received the MBRP program; and control group- CG (34), that was in the waitlist, having received phone monitoring about the hypnotics use during the 8 weeks, while the IG received the intervention. Every participant received a psychiatric consultation for instruction about the hypnotics tapering and a psychoeducational group session based on the Motivational Interviewing about the chronic use of hypnotics, previously to the intervention. We repeated the measures every two months after the intervention, totaling 8 months of follow-up. Twenty eight participants from the CG and 23 participants of the IG concluded the study. Results: Study 1 – Most of the sample (85.3%) was under medical prescription of hypnotics, from those, in 55.6% of the cases, the doctor frequently evaluated the side effects or effects of the medicine on the patients sleep. Although most of them were using under medical prescription, the dependence indices ranged from high to very high in all dependence subscales. The most used medicine was the Zolpidem (41.3%) and the median of the time of hypnotic’s use was 30 months (IQR=51). In the baseline, the level of dispositional mindfulness, especially in the “observe” and “non-reactivity to inner experience” dimensions, was inversely associated to the hypnotic’s dependence in every dimension, except to the “problematic use” dimension. Study 2 – in the clinical trial we observed that the IG reduced the dosage significantly more than the CG in the T1 [b=2,22; CI (0,26;4,19) p=0,027]. This difference was no longer significant on the next follow-ups, once the CG also continued to reduce the use. Regarding the insomnia, there was a significant reduction of its severity in the IG, but not in the CG, on the 3rd [b=4,33; IC (1,75;6,91) p=0,0001] and 4th follow-ups [b=3,65; IC (1,07;6,22) p=0,005], even when the analyses were adjusted by time, group, interaction between time and grou, insomnia severity in the baseline, anxiety (trait), menopause and depression symptoms. Conclusion: The mindfulness abilities, specially “observe” and “non-react” were potential protective factors to hypnotic’s dependence in the cross-sectional study. These data were corroborated by the clinical trial, once the intervention favored the hypnotic’s tapering, also contributing to the reduction of the insomnia severity on the long-term. These data show preliminary evidence on the mindfulness-based interventions for the chronic hypnotic’s use, paving the way for a new therapeutic possibility to the reduction of inappropriate consumption of these medicines. ClinicalTrials.gov Identifier: NCT02127411